Rapid and flexible whole body postural responses are evoked from perturbations to the upper limb during goal-directed reaching - Lowrey, Catherine R. (J Neurophysiol, 2017)
An important aspect of motor control is the ability to perform tasks with the upper limbs while maintaining whole body balance. However, little is known about the coordination of upper limb voluntary and whole body postural control after mechanical disturbances that require both upper limb motor corrections to attain a behavioral goal and lower limb motor responses to maintain whole body balance. The present study identified the temporal organization of muscle responses and center of pressure (COP) changes following mechanical perturbations during reaching. Our results demonstrate that muscle responses in the upper limb are evoked first (∼50 ms), with lower limb muscle activity occurring immediately after, in as little as ∼60 ms after perturbation. Hand motion was immediately altered by the load, while COP changes occurred after ∼100 ms, when lower limb muscle activity was already present. Our secondary findings showed that both muscle activity and COP changes were influenced by behavioral context (by altering target shape, circle vs. rectangle). Voluntary and postural actions initially directed the hand toward the center of both target types, but after the perturbation upper limb and postural responses redirected the hand toward different spatial locations along the rectangle. Muscle activity was increased for both upper and lower limbs when correcting to the circle vs. the rectangle, and these differences emerged as early as the long-latency epoch (∼75–120 ms). Our results demonstrate that postural responses are rapidly and flexibly altered to consider the behavioral goal of the upper limb. NEW & NOTEWORTHY The present work establishes that, when reaching to a target while standing, perturbations applied to the upper limb elicit a rapid response in lower limb muscles. Unlike voluntary movements, postural responses do not occur before corrections of the upper limb. We show the first evidence that corrective postural adjustments are modulated by upper limb behavioral context (target shape). Importantly, this indicates that postural responses take into account upper limb feedback for online control.